Kualitas Pelayanan Publik (Studi Kasus:Pelayanan Tera/Tera Ulang Di Kota Dumai) - hildawati tobing (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2023)
The calibration/recalibration service in Dumai City is the authority of the Dumai City Trade Office under the responsibility of the Kemetrologian Division, especially the calibration/recalibration service section. Based on observations, problems were found, namely: the lack of the number of markers, inadequate test equipment, lack of access to information, and limited service areas. This research aims to determine the quality of The calibration/recalibration services at the Dumai City Trade Office. The theory used is according to Dabholkar (1996) in Al Idrus (2019: 2) which explains that the benchmarks of service quality are: physical aspect, reliability, personal interaction, problem-solving, and policy. Research respondents were employees of the Trade Office and Business Actors. The number of samples was 119 people. Data collection techniques use observation, questionnaires, and interviews. The data analysis method used is a mixed method. The results of the analysis show that the Quality of The calibration/recalibration Services at the Dumai City Trade Office is categorized as good because the score obtained is 8225 in the range of 8,095 - 9,999.